The Lar alkaline igneous complex: Age, mineralogy, chemistry, and isotopes of a potassic post-collisional event in the Eastern Iran Magmatic Belt (Sistan Suture Zone, East Iran) - M. Ghiotto; C. Natali; A. Rabiee; A. Bragagni; E. Braschi; R. Avanzinelli; M. Casalini; S. Ghafaribijar; M. Arvin; F. Rossetti; S. Conticelli (Lithos, 2026)

The VEI7 “Tufo Rosso a Scorie Nere sabatino” caldera-forming eruption (433 ka, Sabatini Volcanic District, Roman Province, Italy): insights from field data and glass geochemistry - A. Frontoni; G. A. R. Gualda; A. Bonamico; R. Cioni; S. Conticelli; G. Giordano (Bulletin of Volcanology, 2026)
The K-alkaline, Quaternary Roman Magmatic Province (RMP) includes several active and quiescent caldera-forming volcanoes along the Italian Tyrrhenian margin, which have erupted tens of intermediate to large volume ignimbrites, poorly studied in terms of erupted volume and associated plumbing system, with few noticeable exceptions like the 40 ka Campanian Ignimbrite from Campi Flegrei. Here we reappraise the 433 ka Tufo Rosso a Scorie Nere sabatino (TRSNs) ignimbrite from the Bracciano caldera. Using new field data, we calculate the erupted DRE volume to be 67–170 km 3 , corresponding to a mass of 0.87–4.35 × 10 14 kg, which classifies the eruption as VEI 7 and magnitude 7, and the second largest identified within the RMP, after 181–265 km 3 DRE of the Campanian Ignimbrite. This new volume estimate is one order of magnitude larger than previously suggested and suggests that the volumes of many other ignimbrites from the RMP may be severely underestimated, potentially qualifying the RMP as an ignimbrite flare-up system. Geochemical characterization of the TRSNs residual glass allows us to test the efficiency of rhyolite-MELTS geobarometry for phonolite compositions and discuss the geometry and structure of the plumbing system leading to the TRSNs caldera-forming event. These data highlight the occurrence of a zoned magma reservoir, which fed first the initial Plinian phase, followed by the main ignimbrite and caldera-forming phase.

Ages, geochemistry and Sr-Nd-Pb isotopes of alkaline potassic volcanic rocks from the Ahar-Arasbaran region (NW Iran): Evidence for progressive evolution of mantle sources during the Neotethyan subduction system - C. Natali; M. Aghazadeh; E. Braschi; R. Avanzinelli; Z. Badrzadeh; G. Bianchini; M. Casalini; S. Agostini; M. Mattei; S. Conticelli (Lithos, 2024)

The Ethiopian subcontinental mantle domains: geochemical evidence from Cenozoic mafic lavas - S. Tommasini; P. Manetti; F. Innocenti; T. Abebe; M. Sintoni; S. Conticelli (Mineralogy and Petrology, 2005)

Crystallization conditions of leucite-bearing magmas and their implications on the magmatological evolution of ultrapotassic magmas: the Vico Volcano, Central Italy - G. Perini; S. Conticelli (Mineralogy and Petrology, 2002)

Source contamination and mantle heterogeneity in the genesis of Italian potassic and ultrapotassic volcanic rocks: Sr-Nd-Pb isotope data from Roman Province and Southern Tuscany - S. Conticelli; M. D'Antonio; L. Pinarelli; L. Civetta (Mineralogy and Petrology, 2002)